Emotion : Pleasure and Pain in the Brain - Kringelbach, Morten L. and Philips, Helen (New York Oxford University Press, 2014)
Emotion provides a clear, contemporary review of our understanding of emotions and their neural basis - what is happening in our brains to make us 'feel the way we do'. It also explores emotional disorders, and how our understanding of emotion can be used to treat a range of psychiatric disorders.
Include Color Illustration and Index
Keywords: Emotions